Aldose reductase inhibitory activity of alcoholic extract of Pedalium murex Linn fruit - Patel D.K.; Kumar R.; Sairam K.; Hemalatha S. (My University, 2025)
Objective: To investigate physico-chemical investigation and aldose reductase inhibitory activity in rat lens aldose reductase (AR) enzyme of the ethanolic extract of fruits of Pedalium murex (P. murex) Linn (Pedaleaceae). Methods: Physico-chemical investigation of ethanolic extract of fruit of the P. murex (EPM) was carried out. EPM was screened for aldose reductase inhibitory activity using rat lens AR enzyme. HPTLC fingerprinting analysis of EPM was performed in chloroform: methanol (8:2) solvent system. Results: Total ash, acid insoluble ash, water soluble ash, alcohol and water soluble extractive value and loss on drying of P. murex were found to be 4.2%, 1.2%, 0.92%, 6.2%, 5.0% and 7.5% respectively. Eleven prominent spots were found to be present in the EPM in HPTLC fingerprint analysis. EPM showed significant level of aldose reductase inhibitory potential [IC 50 value (57.20±3.68) μg/mL]. From the value of V max, K m and K i, it was found that EPM exhibits non-compititive inhibition with AR enzyme. Conclusion: The present study reveals scientific basis of the P. murex, which can be used in the treatment of the cataract disorder. © 2012 Asian Pacific Tropical Biomedical Magazine.